Addressing European Ocean Energy Challenge: The DTOceanPlus Structured Innovation Tool for Concept Creation and Selection - Inès Tunga; Anna Garcia-Teruel; Donald R. Noble; Jillian Henderson (Energies, 2021)
The whole energy system requires renewables that scale and produce reliable, valuable energy at an acceptable cost. The key to increasing the deployment of ocean energy is bringing down development and operating costs. This paper proposes a structured approach to innovation in ocean energy systems that would spur innovation and expand the market for ocean energy. This approach can be used by a wide range of stakeholders—including technology and project developers and investors—when considering creating or improving designs. The Structured Innovation design tool within the DTOceanPlus suite is one of a kind beyond the current state-of-the-art. It enables the adaptation and integration of systematic problem-solving tools based on quality function deployment (QFD), the theory of inventive thinking (TRIZ), and the failure modes and effects analysis (FMEA) methodologies for the ocean energy sector. In obtaining and assessing innovative concepts, the integration of TRIZ into QFD enables the designers to define the innovation problem, identifies trade-offs in the system, and, with TRIZ as a systematic inventive problem-solving methodology, generates potential design concepts for the contradicting requirements. Additionally, the FMEA is used to assess the technical risks associated with the proposed design concepts. The methodology is demonstrated using high-level functional requirements for a small array of ten tidal turbines to improve the devices layout and power cabling architecture. The Structured Innovation design tool output comprises critical functional requirements with the highest overall impact and the least organisational effort to implement, along with appropriate alternative solutions to conflicting requirements.